1986
DOI: 10.1073/pnas.83.13.4923
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and pharmacological characterization of an extremely potent and selective nonpeptide cholecystokinin antagonist.

Abstract: 3S(-)-N-(2,3-dihydro-1-methyl-2-oxo-5-phenyl-IH-1,4-benzodiazepine-3-yl)-lH-indole-2-carboxamide (L-364,718) interacted in a competitive manner with rat pancreatic cholecystokinin (CCK) receptors as determined by Scatchard analysis of the specific binding of '21I-labeled CCK. The affinity of L-364,718 for both pancreatic (IC50, 81 pM) and gallbladder (IC50, 45 pM) CCK receptors in radioligand binding assays greatly exceeded that of other reported nonpeptide CCK antagonists and was similar to that of CCK itsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
174
1

Year Published

1989
1989
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 439 publications
(190 citation statements)
references
References 30 publications
(10 reference statements)
15
174
1
Order By: Relevance
“…The effect of this CCKB/gastrin antagonist was relatively weak compared to PD 136450, whilst the selective CCKA antagonist devazepide was inactive at up to 300pumolkg-1 against the three stimulants. This latter observation is in keeping with the low affinity of devazepide for both the gastrin, and brain CCKB receptors (Chang & Lotti, 1986;Evans et al, 1986). However, our results with devazepide are in conflict with those in a similar study by Hirst et al (1991).…”
Section: Stimulation Ofgastric Acid Secretioncontrasting
confidence: 57%
See 2 more Smart Citations
“…The effect of this CCKB/gastrin antagonist was relatively weak compared to PD 136450, whilst the selective CCKA antagonist devazepide was inactive at up to 300pumolkg-1 against the three stimulants. This latter observation is in keeping with the low affinity of devazepide for both the gastrin, and brain CCKB receptors (Chang & Lotti, 1986;Evans et al, 1986). However, our results with devazepide are in conflict with those in a similar study by Hirst et al (1991).…”
Section: Stimulation Ofgastric Acid Secretioncontrasting
confidence: 57%
“…All other antagonists tested had no effect upon basal acid secretion. Recently, non-peptide agents of the benzodiazepine structure with high affinity for peripheral CCKA receptors and only low affinity for gastrin and CCKB receptors have been described (Chang et al, 1985;Chang & Lotti, 1986). The related compound with the reverse profile of affinity, L-365,260, was subsequently described (Bock et al, 1989;Lotti & Chang, 1989 active in producing a dose-dependent block of pentagastrininduced acid secretion in the anaesthetized rat, confirming observations of Lotti & Chang (1989) in the anaesthetized mouse and conscious rat following oral or intraduodenal administration.…”
Section: Stimulation Ofgastric Acid Secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…CCK receptors are classified into type A (peripheral) and type B (central), depending on the structural specificity expressed and the relative affinities for various members of the CCK-gastrin family (Moran et al, 1986). Recently, highly potent and specific antagonists for the peripheral CCKA receptors have been reported (Makovec et al, 1985;Chang & Lotti, 1986;Akiyama & Otsuki, 1994). MK-329 (formerly termed L-364,718) is considered the most potent and highly specific CCK antagonist and is used to characterize the peripheral CCKA receptors (Otsuki et al, 1988;Niederau et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…CCK interacts with at least two distinct types of receptor (Innis & Snyder, 1980;Moran et al, 1986;Wank et al, 1992): CCKB receptors, which represent the predominant form in the rodent CNS (Pelaprat et al, 1987;Hill & Woodruff, 1990) and CCKA receptors, the abundant form in peripheral tissues (Zetler, 1984;Van Dijk et al, 1984;Chang & Lotti, 1986) but are also found in discrete nuclei of the CNS (Hill et al, 1987a;. Molecular cloning and pharmacological studies have demonstrated a close relationship between CCKB and gastrin receptors found mainly in the parietal cells of the gastric mucosa (Chang et al, 1989;Pisegna et al, 1992;Hunter et al, 1993).…”
Section: Introductionmentioning
confidence: 99%